The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/ange.201912338
|View full text |Cite
|
Sign up to set email alerts
|

Single Electron Transfer to Diazomethane–Borane Adducts Prompts C−H Bond Activations

Abstract: While (Ph 2 CN 2 )B(C 6 F 5 ) 3 is unstable,single electron transfer from Cp* 2 Co affords the isolation of stable products [Cp* 2 Co][Ph 2 CNNHB(C 6 F 5 ) 3 ] 1 and [Cp*Co(C 5 Me 4 CH 2 B-(C 6 F 5 ) 3 )] 2.The analogous combination of Ph 2 CN 2 and BPh 3 showed no evidence of adduct formation and yet single electron transfer from Cp* 2 Cr affords the species [Cp* 2 Cr]-[PhC(C 6 H 4 )NNBPh 3 ] 3 and [Cp* 2 Cr][Ph 2 CNNHBPh 3 ] 4. Computations showed both reactions proceed via transient radical anions of the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…A single electron transfer from Co II to the diazomethane-borane adduct Ph 2 CN 2 B(C 6 F 5 ) 3 was proposed to account for the formation of [Cp*Co(C 5 Me 4 CH 2 B(C 6 F 5 ) 3 )]. 13 Furthermore, in 2020, Stephan and co-workers disclosed that a stoichiometric reaction between Ph 2 CN 2 and the oxygen-linked geminal FLP complexes R 2 POBcat (R = t -Bu, mesityl) (derived from the reaction between phosphine oxides t- Bu 2 P(O)H/Mes 2 P(O)H and ClBcat) afforded Ph 2 C(N 2 )BcatOPR 2 . 14 Formation of these BOPN 2 five-membered heterocyclic compounds was confirmed by single crystal X-ray diffraction.…”
Section: Activation Of Diazo Compounds Using Stoichiometric B(ar F )mentioning
confidence: 99%
See 1 more Smart Citation
“…A single electron transfer from Co II to the diazomethane-borane adduct Ph 2 CN 2 B(C 6 F 5 ) 3 was proposed to account for the formation of [Cp*Co(C 5 Me 4 CH 2 B(C 6 F 5 ) 3 )]. 13 Furthermore, in 2020, Stephan and co-workers disclosed that a stoichiometric reaction between Ph 2 CN 2 and the oxygen-linked geminal FLP complexes R 2 POBcat (R = t -Bu, mesityl) (derived from the reaction between phosphine oxides t- Bu 2 P(O)H/Mes 2 P(O)H and ClBcat) afforded Ph 2 C(N 2 )BcatOPR 2 . 14 Formation of these BOPN 2 five-membered heterocyclic compounds was confirmed by single crystal X-ray diffraction.…”
Section: Activation Of Diazo Compounds Using Stoichiometric B(ar F )mentioning
confidence: 99%
“…However, in 2017, Stephan and co-workers demonstrated that B(C 6 F 5 ) 3 can activate diphenydiazomethane as Lewis acidic boranes readily interact with the nitrogen functionality of diazo compounds, leading to the formation of Lewis acid−base adducts. 12 The stoichiometric reaction between Ph 2 CN 2 and B(C 6 13 Furthermore, in 2020, Stephan and co-workers disclosed that a stoichiometric reaction between Ph 2 CN 2 and the oxygen-linked geminal FLP complexes R 2 POBcat (R = t-Bu, mesityl) (derived from the reaction between phosphine oxides t-Bu 2 P(O)H/ Mes 2 P(O)H and ClBcat) afforded Ph 2 C(N 2 )BcatOPR 2 . 14 Formation of these BOPN 2 five-membered heterocyclic compounds was confirmed by single crystal X-ray diffraction.…”
Section: ■ Activation Of Diazo Compounds Using Stoichiometric B(ar F )mentioning
confidence: 99%
“…Attempts to replace the transition metals resulted in the first boron‐based bimolecular catalysts within the framework of frustrated Lewis pairs (FLP) or by exploiting the ambiphilic nature of the boron atom having empty and filled orbitals under certain conditions (being in the B (I) instead of the common B (III) state, Scheme 1). [26–37] A recent computational study employed 2,3’‐bipyridine to mediate intra‐molecular tetraboration of dinitrogen [36] . In a conceptual density functional theory (DFT) study on a peri ‐substituted bond activator molecule, we could recently show that N 2 ‐splitting could potentially also be conducted intra‐molecularly by tripodal light atom molecules containing only earth abundant C, H, P, and Si atoms [38] .…”
Section: Introductionmentioning
confidence: 99%
“…However, a single electron transfer (SET) process was assumed to be operative from Cp*2Co to Ph2CN2B(C6F5)3 for the formation of [Cp*Co(C5Me4CH2B(C6F5)3)] (Scheme 1). 27 In 2020, Stephan also examined that frustrated Lewis pairs (FLPs) R2POBcat (R = t Bu, mesityl, cat = catechol) derived from phosphine oxides and ClBcat reacted with Ph2CN2 to form the compound Ph2C(N2)BcatOPR2 (R = t Bu) with 87% yield (Scheme 1). 28 Unfortunately, a problem with isolation prevented the purification of the compound Ph2C(N2)BcatOPR2 (R = mesityl), nevertheless single crystal X-ray analysis helped to assign the structure of the compound.…”
Section: Template For Synthesis Thiemementioning
confidence: 99%